2017
DOI: 10.1111/jora.12309
|View full text |Cite
|
Sign up to set email alerts
|

Same‐Ethnic, Interethnic, and Interracial Friendships Among Asian Early Adolescents

Abstract: This study examined the psychological functions of three friendship types (i.e., same-ethnic, interethnic and interracial) in a sample of 785 sixth grade Asian students (Mage=11.5 years). Participants listed their friends in 6th grade and whether each nominated friend was the same or a different ethnic group. They also reported on their ethnic identity, intergroup relations, and perceived school safety. Results showed that same-ethnic friendships were related to stronger ethnic identity and interracial friends… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 31 publications
3
17
0
Order By: Relevance
“…Our most important finding was that peer's ethnicity matters for peer influence effects on ERI content. This finding is not only consistent with the SIT perspective but also supports the notion that same‐ and cross‐ethnic friends serve different functions (Chen & Graham, ; Jugert & Feddes, ). Our findings also support previous research that same‐ethnic friendships are more relevant than cross‐ethnic friendships for ERI development (Kiang & Fuligni, ; Syed & Juan, ).…”
Section: Discussionsupporting
confidence: 87%
“…Our most important finding was that peer's ethnicity matters for peer influence effects on ERI content. This finding is not only consistent with the SIT perspective but also supports the notion that same‐ and cross‐ethnic friends serve different functions (Chen & Graham, ; Jugert & Feddes, ). Our findings also support previous research that same‐ethnic friendships are more relevant than cross‐ethnic friendships for ERI development (Kiang & Fuligni, ; Syed & Juan, ).…”
Section: Discussionsupporting
confidence: 87%
“…In our review of existing literature, terminology of race and ethnicity is used in accordance with the original authors' descriptions. Chen and Graham (2017) found that adolescents' same-race friendships (including same-and different-ethnic) were linked to higher ethnic identity, and both different-ethnic and different-race friendships were linked to better intergroup relations.…”
Section: Introductionmentioning
confidence: 94%
“…However, the vast literature on peer relationships can inform our hypotheses and approach. This peer literature suggests positive correlations between ethnic identity and same-ethnic friendships (Chen & Graham, 2017;Graham et al, 2014;Yip et al, 2013). Among diverse adolescents, Graham and colleagues (2014) demonstrated that adolescents with higher levels of private regard reported greater numbers of same-ethnic friends.…”
Section: Correlates Of Ethnicity-related Dating Preferences: the Rolementioning
confidence: 99%
See 1 more Smart Citation
“…B. Brown, Eicher, & Petrie, 1986), most research on same- and cross-ethnic friendship preferences amongst Asian American youth has been conducted with adolescents (Benner & Wang, 2017; Chen & Graham, 2015, 2017). For example, Chen and Graham (2015) found that cross-ethnic friendships in Asian American early adolescents are more likely to be with European American peers and are associated with greater intent to engage in activities with members of that particular ethnic group (Chen & Graham, 2015).…”
Section: Developmental Differences In Attitudes and Perceptionsmentioning
confidence: 99%